2008
DOI: 10.1007/s11255-008-9360-9
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in eGFR in patients with chronic kidney disease attending a nephrology clinic

Abstract: Referral to a nephrology clinic can lead not only to arrest of progression of CKD but also to regression/improvement. Early referral is a positive predictive factor for improvement in eGFR, which emphasizes the importance of such referral. The previously held idea that, once established, CKD progresses invariably is not valid anymore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…This recommendation has been validated in several Caucasian and African-American patient populations [13][14][15][16][17][18][19][20][21][22]. Few reports exist among native Africans validating prediction equations in the prediction of the GFR [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation has been validated in several Caucasian and African-American patient populations [13][14][15][16][17][18][19][20][21][22]. Few reports exist among native Africans validating prediction equations in the prediction of the GFR [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings appear to indicate that the broad application of the CKD-EPI equation may result in a perceptible change in both the number and characteristics of CKD patients in healthcare systems, which may affect treatment planning and clinical decision making. This change may be accelerated by widespread implementation of calculators using the CKD-EPI equation for GFR reporting (15).…”
Section: Key Findingsmentioning
confidence: 99%
“…Without the benefits of long-term follow-up, it is unclear from our study whether the differences in classification of CKD patients using CKD-EPI would result in any significant benefits or risks to patients. For instance, a potential ramification of the new equation, accompanied by the same standards for CKD classification, may be that younger patients are not identified with kidney dysfunction as rapidly, whereas early diagnosis of CKD may have important benefits to slow the progression of disease in these patients (15,(17)(18)(19). Although in general, younger patients are more frequently diagnosed with CKD on the basis of proteinuria rather than eGFR, only a minority of patients in our study population had ICD-9 codes indicative of kidney disease (20).…”
Section: Key Findingsmentioning
confidence: 99%
“…A recent paper examined the initial characteristics of patients referred in various stages of CKD and tried to identify factors associated with subsequent changes in estimated glomerular filtration rate (eGFR). They concluded that early referral is a positive predictive factor for improvement in eGFR, thus emphasizing the importance of such referral [92]. Ifudu et al reported that, when CKD patients were referred to a nephrologist at an early stage, they approached RRT with well-maintained renal function [93], and Innes et al suggested that early initiation of RRT led to an improvement in short-term prognosis [94].…”
Section: Role Of Predialysis Trainingmentioning
confidence: 99%